Preparation of low-density vermiculite-based nano zero-valence confinement iron-manganese composite complex and application of low-density vermiculite-based nano zero-valence confinement iron-manganese composite complex in advanced treatment of novel pollutants
By preparing low-density vermiculite-based nano zero-valent limited-domain iron-manganese composite complex, the problems of existing nano zero-valent iron composites are easily passivated in the air and slow catalytic reaction rate are achieved, and a new efficient and economical pollution is achieved Degradation effect of substances.
Patent Information
- Application Number
- CN202411571512.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
AI Technical Summary
Existing nano zero-valent iron composites are easily passivated, easily agglomerated, slow catalytic reaction rate and expensive, making it difficult to effectively deal with new pollutants.
Low-density vermiculite-based nano zero-valent limited-domain iron-manganese composite complex is prepared by calcining, reducing calcining and vacuum quenching to form a catalyst with high specific surface area and nano-domain limited-domain effect.
It significantly improves the rate and activity of the catalytic reaction, can efficiently degrade new pollutants, and is cheap, and is suitable for deep treatment of new pollutants.
Smart Images

Figure CN119425797A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water treatment, and specifically relates to the preparation of a low-density vermiculite-based nanometer zero-valent confined iron-manganese composite complex and its application in deep treatment of new pollutants. Background Art
[0002] Emerging pollutants refer to a class of chemical substances that can be detected in the environment and natural ecosystems and can pose greater risks and hidden dangers to human health and environmental safety even at low doses. Emerging pollutants that have attracted widespread attention at home and abroad mainly include antibiotics, flame retardants and fluorides that are controlled by international conventions. They generally have the characteristics of more serious hazards, more hidden risks, environmental persistence, widespread sources, and complex governance.
[0003] Advanced oxidation technology is one of the commonly used purification methods for treating new pollutants, and the development of efficient and stable catalysts is the key to improving its purification effect. In recent years, nanocatalysts (such as nano zero-valent iron composites, nano cobalt composites, nano copper composites and nano manganese composites) prepared by liquid phase reduction method using iron salts, cobalt salts, copper salts and manganese salts as raw materials have been widely used in the treatment of new pollutants, although they show high degradation efficiency. However, these materials have defects such as easy agglomeration, easy deactivation in the air, slow catalytic reaction rate, and high price, and there are many problems in practical applications. Therefore, the development of green, environmentally friendly, low-cost and highly active mineral catalysts based on nano-confinement is to solve the main key problems faced by current advanced oxidation technology in the treatment of new pollutants.
[0004] Nanominerals are the basic units that make up rocks and mineral deposits, and their existence form and properties have a significant impact on a variety of geological processes. Nanominerals have a small particle size, a large specific surface area, a high surface energy, and a high surface atomic ratio, so their surface properties and chemical activity are different from those of large-sized mineral particles. In interfacial reactions such as catalysis, nanominerals exhibit unique reactivity and mechanisms, making them excellent catalysts. In order to further improve the catalytic reaction activity of nanominerals, our team previously used iron-containing nanominerals, cobalt-containing nanominerals, copper-containing nanominerals, and manganese-containing nanominerals to form nanostructured zero-valent iron composites, nanostructured cobalt composites, nanostructured zero-valent copper composites, and nanostructured manganese composites with high specific surface areas during hydrogen reduction roasting. These materials have high reduction reaction activity, high thermochemical activity, and low redox potential, which makes them potentially suitable for catalytic degradation of new pollutants. However, studies have found that they are easily passivated in the air, resulting in a reduction in active sites, and the materials are prone to agglomeration and inactivation, thereby reducing the rate of catalytic degradation. Therefore, it is urgent to develop new nano-confined mineral functional materials to improve the catalytic degradation efficiency on the one hand and accelerate the catalytic degradation rate on the other hand, which is the key to solving the deep treatment of new pollutants. Summary of the invention
[0005] Nano-minerals exist stably in nano-size in the surface environment, mainly including manganese-containing nano-minerals and iron-containing nano-minerals. In recent years, the research on using these nano-minerals for environmental pollution remediation has received extensive attention.
[0006] my country has rich manganese-containing nano-mineral resources, most of which are low-grade deposits and often contain impurities such as dolomite, pyrite, clay minerals, quartz and organic matter. The particles of manganese-containing nano-minerals are mostly nano-scale, with low crystallinity and large internal surface area. Manganese-containing nano-minerals mainly include pyrolusite, psilomelane and rhodochrosite, whose MnO6 octahedrons form a single chain structure by sharing edges and extend along the c-axis to form a pore structure. my country is rich in iron-containing nano-mineral resources, mainly poor ores, including limonite, siderite, hematite and pyrite. The main component of limonite is goethite, which is a nano-needle crystal and belongs to cryptocrystalline goethite. Hematite has a nano-sheet structure and exists in the form of oolitic aggregates. These aggregates are formed by the layer-by-layer condensation of hematite and have a roe-like spherical structure. The main component of siderite is ferrous carbonate, which is in the form of crystalline particles or dense blocks, gels and spheres without obvious crystals.
[0007] Since the particle sizes of iron-containing nano-minerals and manganese-containing nano-minerals are all at the nanoscale, this leads to difficulties in mineral processing, and these nano-mineral resources have not been reasonably utilized. Therefore, how to effectively utilize these nano-mineral resources and develop functional nano-confined mineral materials based on deep treatment of new pollutants is of great practical significance.
[0008] In view of the deficiencies in the prior art, the present invention provides a method for preparing a low-density vermiculite-based nanometer zero-valent confined iron-manganese composite complex and its application in deep treatment of new pollutants.
[0009] The preparation method of the low-density vermiculite-based nanometer zero-valent confined iron-manganese composite complex of the present invention comprises the following steps:
[0010] Step 1: The vermiculite mineral, the manganese-containing nano-mineral and the iron-containing nano-mineral are crushed through a 200-mesh sieve respectively to obtain vermiculite mineral powder, manganese-containing nano-mineral powder and iron-containing nano-mineral powder with a particle size of ≤0.075 mm.
[0011] Step 2: calcining the vermiculite mineral powder at 500-1000° C. in an air atmosphere for 2-5 hours to obtain expanded vermiculite mineral powder.
[0012] Step 3: Mix the expanded vermiculite mineral powder, the manganese-containing nano-mineral powder and the iron-containing nano-mineral powder, evacuate and let stand for 12-24 hours, the vacuum degree range is 0.1Pa-10Pa, this process can accelerate the ion exchange of iron and manganese ions, and enter the interlayer domain in the expanded vermiculite mineral; then reduce and calcine the composite material in a hydrogen atmosphere, the calcination temperature is 500-1000°C, and the calcination time is 2-5 hours to obtain a vermiculite-based nano zero-valent confined iron-manganese composite material.
[0013] Furthermore, the mass ratio of the expanded vermiculite mineral powder, the manganese-containing nano-mineral powder and the iron-containing nano-mineral powder is 1-5:1-5:1.
[0014] Step 4: Mix the vermiculite-based nano zero-valent confined iron-manganese composite material with the thiophene carboxylic acid ligand, evacuate and let stand for 12-24 hours, the vacuum degree range is 0.1Pa-10Pa, this process allows the thiophene carboxylic acid ligand to enter the interlayer domain of the vermiculite-based nano zero-valent confined iron-manganese composite material to obtain a low-density vermiculite-based nano zero-valent confined iron-manganese composite complex.
[0015] The iron-containing nano-minerals include limonite, hematite, pyrite and siderite; the manganese-containing nano-minerals include pyrolusite, psilomelane and rhodochrosite; and the vermiculite mineral is a natural vermiculite mineral.
[0016] The carboxylic acid group is adjacent to the sulfur atom in the thiophene heterocyclic ring of the thiophene carboxylic acid ligand.
[0017] Furthermore, the thiophene carboxylic acid ligand is selected from any one of 2,5-thiophenedicarboxylic acid, 5-methyl-2-thiophenecarboxylic acid, 4-bromo-2-thiophenecarboxylic acid, 5-chloro-2-thiophenecarboxylic acid, and 5-bromo-2-thiophenecarboxylic acid.
[0018] Furthermore, the mass ratio of the vermiculite-based nano zero-valent confined iron-manganese composite material to the thiophene carboxylic acid ligand is 1-5:1, and more preferably 10:3-5.
[0019] Furthermore, the vermiculite-based nano zero-valent confined iron-manganese composite material is mixed with thiophene carboxylic acid ligands, evacuated and allowed to stand for 12-24 hours, the vacuum degree ranges from 0.1Pa to 10Pa, and the pH value of the solution system is 2-12, to obtain a low-density vermiculite-based nano zero-valent confined iron-manganese composite complex.
[0020] The invention discloses an application of the low-density vermiculite-based nanometer zero-valent confined iron-manganese composite complex in deep treatment of new pollutants.
[0021] Specifically, low-density vermiculite-based nano zero-valent confined iron-manganese complex is mixed with persulfate for deep treatment of new pollutants.
[0022] In the above treatment system, the concentration of low-density vermiculite-based nano zero-valent confined iron-manganese complex is 0.1-10 g / L, the concentration of persulfate is 1-10 g / L, and the concentration of new pollutants is 0.1-1000 mg / L.
[0023] The persulfate is peroxymonosulfate or peroxydisulfate.
[0024] The novel pollutants include at least one of antibiotics, flame retardants, and fluorides; more preferably, they include one or more of oxytetracycline, cyclotriphosphazene, and diflorasone.
[0025] The beneficial effects of the present invention are embodied in the following aspects:
[0026] 1. The present invention utilizes vermiculite minerals, iron-containing nano-minerals and manganese-containing nano-minerals commonly found in natural environments, which have significant advantages such as low cost. Expanded vermiculite is used as a substrate, and transition metal ions in iron-containing nano-minerals and manganese-containing nano-minerals are allowed to enter the interlayer domain of expanded vermiculite minerals by vacuuming, and reduction roasting treatment is performed under a hydrogen atmosphere, and expanded vermiculite minerals are composited with nano-zero-valent iron and nano-manganese to form a nano-confinement effect, which can effectively overcome the agglomeration phenomenon of nano-zero-valent iron and nano-manganese. Subsequently, an organic ligand is allowed to enter the interlayer domain of expanded vermiculite-based nano-confinement zero-valent iron-manganese composite materials by vacuuming and impregnation, and a low-density vermiculite-based nano-zero-valent confined iron-manganese mineral composite complex is obtained, which has high activity and can significantly accelerate the rate of the catalytic reaction.
[0027] 2. The catalytic reaction system constructed by combining low-density vermiculite-based nano zero-valent confined iron-manganese composite complexes with persulfate can generate active species with sulfate radicals, hydroxyl radicals and singlet oxygen as the main components. These active species can effectively catalyze the degradation of new pollutants. The degradation process of new pollutants involves the interfacial electron transfer of low-density vermiculite-based nano zero-valent confined iron-manganese composite complexes, which is an oxidation-reduction reaction. Compared with the vermiculite-based nano zero-valent confined iron-manganese composite material without grafted ligands and the persulfate catalytic reaction system, the oxidation rate is significantly improved. This material shows good application potential in the purification of new pollutants.
[0028] 3. Low-density vermiculite-based nano-zero-valent confined iron-manganese composite complexes have significant nano-confined ligand effects. Ligands can form σ bonds with low-density vermiculite-based nano-zero-valent confined iron-manganese dual-center metals, while ligands with appropriate symmetry orbitals can form σ-π bonds with dual transition metals in low-density vermiculite composite nano-zero-valent confined iron-manganese. Ligands that form σ bonds can usually provide electrons to the central dual metals, while ligands that form σ-π bonds generally accept electrons from dual-center low-density vermiculite composite nano-zero-valent confined iron-manganese. This electron transfer effect will cause the electron density of the dual-center low-density vermiculite composite nano-zero-valent confined iron-manganese composite material to change, thereby affecting its bonding strength with other ligands and the speed of related catalytic reactions.
[0029] 4. The principle of low-density vermiculite-based nano zero-valent confined iron-manganese complex in catalytic degradation of new pollutants in wastewater is to change the diatomic electronic structure of the dual-center low-density vermiculite-based nano zero-valent confined iron-manganese composite material through coordination field effect, nano confinement effect and steric effect, thereby regulating its reaction activity. The introduction of organic ligands can broaden the pH range of the catalytic reaction, enhance the activity of low-density vermiculite-based nano zero-valent confined iron-manganese, and improve the effect of advanced oxidation technology in the catalytic degradation of new pollutants. Thiophene carboxylic acid ligands are bidentate S heterocyclic carboxylic acid ligands. Unlike O and N coordinated atoms, S atoms have empty 3d orbitals and can coordinate with low-density vermiculite-based nano zero-valent confined iron-manganese to form feedback π bonds. This coordination effect can increase the reduction potential of low-density vermiculite-based nano zero-valent confined iron-manganese and promote its reaction with persulfate, thereby achieving deep treatment of new pollutants.
[0030] 5. Low-density vermiculite-based nano-zero-valent confined iron-manganese complexes are mainly porous and layered structures with large specific surface area and high porosity. The metal atoms in the low-density vermiculite-based nano-zero-valent confined iron-manganese complexes carry static charges or are in different oxidation states, thus showing characteristics such as ion exchange, pore effect, redox effect, nano-confinement effect and catalytic effect. During the hydrogen reduction roasting process, the particle size of the nano-minerals decreases, resulting in a considerable proportion of atoms being located on the surface of the particles, and the electrical properties also change. This makes the low-density vermiculite-based nano-zero-valent confined iron-manganese complexes exhibit different catalytic activity from large-sized minerals. Specifically, the reduction in particle size not only increases the specific surface area of the nano-confined minerals, but also increases the surface charge density, the number of unsaturated coordinated atoms on the surface, the surface defect density and the surface energy. Due to its smaller particle size, high surface energy and larger surface atom ratio, the low-density vermiculite-based nano-zero-valent confined iron-manganese complexes exhibit different surface properties, chemical activity and electrical properties from traditional large-sized catalysts. In interfacial reactions such as catalytic reactions, low-density vermiculite-based nano-zero-valent confined iron-manganese complexes exhibit special reaction activity and mechanisms, thereby increasing their affinity for new pollutants. Therefore, low-density vermiculite-based nano-zero-valent confined iron-manganese complexes have broad application prospects in the treatment of new pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the XRD pattern of pyrite.
[0032] Figure 2 This is the XRD pattern of limonite.
[0033] Figure 3 This is the XRD pattern of siderite.
[0034] Figure 4 This is the XRD pattern of manganese minerals.
[0035] Figure 5 SEM images of limonite (A, B).
[0036] Figure 6 It is the SEM image of Example 1, wherein AD is different magnifications.
[0037] Figure 7 These are SEM images of Example 2, wherein AC are at different magnifications.
[0038] Figure 8 It is the SEM picture of Example 3, wherein AD is different magnifications.
[0039] Fig. 9 These are SEM images of Example 4, wherein AC are at different magnifications.
[0040] Fig.10 These are SEM images of Example 5, wherein AC are at different magnifications.
[0041] Fig.11 These are SEM images of Example 6, wherein AC are at different magnifications.
[0042] Fig.12 These are SEM images of manganese minerals, where AD are different magnifications.
[0043] Fig.13 This is a crystal structure model diagram of vermiculite mineral.
[0044] Fig.14 This is a crystal structure model diagram of limonite.
[0045] Fig.15 This is a diagram of the crystal structure model of siderite.
[0046] Fig.16 This is a model diagram of the crystal structure of pyrite.
[0047] Fig.17 This is a model diagram of the crystal structure of hematite.
[0048] Fig.18 This is a model diagram of the crystal structure of manganese minerals.
[0049] Fig.19 These are SEM images of vermiculite ore, where AD represents different magnifications.
[0050] Fig. 20 These are SEM images of vermiculite mineral calcined at 400°C, where AD are different magnifications.
[0051] Fig.21 These are SEM images of vermiculite mineral calcined at 500°C, where AD are different magnifications.
[0052] Fig. 22 These are SEM images of vermiculite mineral calcined at 600°C, where AD are different magnifications.
[0053] Fig.23 These are SEM images of vermiculite mineral calcined at 700°C, where AD are different magnifications.
[0054] Fig.24 These are SEM images of vermiculite mineral calcined at 800°C, where AD are different magnifications.
[0055] Fig.25 These are SEM images of vermiculite mineral calcined at 900°C, where AD are different magnifications.
[0056] Fig.26These are SEM images of vermiculite mineral calcined at 1000°C, where AD are different magnifications.
[0057] Fig. 27 A-physical picture of natural vermiculite mineral; B-physical picture of expanded vermiculite mineral; C-physical picture of natural limonite; D-physical picture of manganese mineral; E-physical picture of low-density vermiculite-based nano-zero-valent confined iron-manganese composite complex.
[0058] Fig.28 Actual pictures of vermiculite mineral (A), expanded vermiculite (B) and low-density vermiculite-based nano-zero-valent confined iron-manganese complex (C) in water. DETAILED DESCRIPTION
[0059] Embodiment 1:
[0060] 1. The vermiculite mineral, limonite and pyrolusite are crushed through a 200-mesh sieve to obtain vermiculite mineral powder, limonite powder and pyrolusite powder with a particle size of ≤0.075 mm.
[0061] 2. The vermiculite mineral powder was calcined at 500° C. for 4 hours in an air atmosphere to obtain expanded vermiculite mineral powder.
[0062] 3. Fully mix expanded vermiculite mineral powder, limonite powder and pyrolusite powder in a mass ratio of 1:1:1 to obtain a mineral mixture material; vacuumize and let stand for 12 hours with a vacuum degree of 1 Pa to accelerate the ion exchange of iron and manganese ions, which enter the interlayer domain of the expanded vermiculite mineral to obtain a mineral mixture material.
[0063] 4. The mineral mixture is reduction-calcined at a temperature of 500° C. in a hydrogen atmosphere for 4 hours to obtain a vermiculite-composite nano-zero-valent confined iron-manganese composite material.
[0064] 5. The vermiculite composite nano zero-valent confined iron-manganese composite material and 2,5-thiophene dicarboxylic acid were placed in a mass ratio of 1:1, vacuumed and left to stand for 12 hours at a vacuum degree of 1 Pa, so that 2,5-thiophene dicarboxylic acid entered the interlayer domain of the vermiculite composite nano zero-valent confined iron-manganese composite material to obtain a low-density vermiculite-based nano zero-valent confined iron-manganese composite complex. The specific surface area of the composite material is 168m 2 / g.
[0065] Embodiment 2:
[0066] 1. The vermiculite mineral, hematite and pyrolusite are crushed through a 200-mesh sieve to obtain vermiculite mineral powder, hematite powder and pyrolusite powder with a particle size of ≤0.075 mm.
[0067] 2. The vermiculite mineral powder was calcined at 600° C. in an air atmosphere for 4 hours to obtain expanded vermiculite mineral powder.
[0068] 3. Fully mix expanded vermiculite mineral powder, hematite powder and pyrolusite powder in a mass ratio of 2:2:1, evacuate and let stand for 12 hours at a vacuum degree of 3Pa to accelerate the ion exchange of iron and manganese ions into the interlayer domain of the expanded vermiculite mineral to obtain a mineral mixture.
[0069] 4. The mineral mixture is reduction-calcined at a temperature of 600° C. in a hydrogen atmosphere for 4 hours to obtain a vermiculite-composite nano-zero-valent confined iron-manganese composite material.
[0070] 5. The vermiculite composite nano zero-valent confined iron-manganese composite material and 2,5-thiophenedicarboxylic acid were placed in a mass ratio of 2:1 and allowed to stand for 12 hours at a vacuum degree of 3 Pa, so that 2,5-thiophenedicarboxylic acid entered the interlayer domain of the vermiculite composite nano zero-valent confined iron-manganese composite material to obtain a low-density vermiculite-based nano zero-valent confined iron-manganese composite complex. The specific surface area of the composite material is 154 m 2 / g.
[0071] Embodiment 3:
[0072] 1. The vermiculite mineral, siderite and psilomelane are crushed through a 200-mesh sieve to obtain vermiculite mineral powder, siderite powder and psilomelane powder with a particle size of ≤0.075 mm.
[0073] 2. The vermiculite mineral powder was calcined at 700° C. in an air atmosphere for 4 hours to obtain expanded vermiculite mineral powder.
[0074] 3. Fully mix expanded vermiculite mineral powder, siderite powder and pyrolusite powder in a mass ratio of 5:2:1, evacuate and let stand for 12 hours at a vacuum degree of 5 Pa to accelerate the ion exchange of iron and manganese ions into the interlayer domain of the expanded vermiculite mineral to obtain a mineral mixture.
[0075] 4. The mineral mixture is reduction-calcined at a temperature of 700° C. in a hydrogen atmosphere for 4 hours to obtain a vermiculite-composite nano-zero-valent confined iron-manganese composite material.
[0076] 5. The vermiculite composite nano zero-valent confined iron-manganese composite material and 5-methyl-2-thiophenecarboxylic acid were vacuumed and left to stand for 12 hours at a mass ratio of 3:1. The vacuum degree range was 5Pa, so that 2,5-thiophene dicarboxylic acid entered the interlayer domain of the vermiculite composite nano zero-valent confined iron-manganese composite material to obtain a low-density vermiculite-based nano zero-valent confined iron-manganese composite complex. The specific surface area of the composite material was 172m 2 / g.
[0077] Embodiment 4:
[0078] 1. The vermiculite mineral, pyrite and psilomelane are crushed through a 200-mesh sieve to obtain vermiculite mineral powder, pyrite powder and psilomelane powder with a particle size of ≤0.075 mm.
[0079] 2. The vermiculite mineral powder was calcined at 800°C in an air atmosphere for 4 hours to obtain expanded vermiculite mineral powder.
[0080] 3. Fully mix expanded vermiculite mineral powder, pyrite powder and pyrolusite powder in a mass ratio of 5:5:1, evacuate and let stand for 12 hours at a vacuum degree of 7Pa to accelerate the ion exchange of iron and manganese ions into the interlayer domain of the expanded vermiculite mineral to obtain a mineral mixture.
[0081] 4. The mineral mixture is reduction-calcined at a temperature of 800° C. in a hydrogen atmosphere for 4 hours to obtain a vermiculite-composite nano-zero-valent confined iron-manganese composite material.
[0082] 5. The vermiculite composite nano zero-valent confined iron-manganese composite material and 4-bromo-2-thiophenecarboxylic acid were placed in a mass ratio of 4:1 and vacuumed for 12 hours at a vacuum degree of 7 Pa to allow 2,5-thiophenedicarboxylic acid to enter the interlayer domain of the vermiculite composite nano zero-valent confined iron-manganese composite material to obtain a low-density vermiculite-based nano zero-valent confined iron-manganese composite complex. The specific surface area of the composite material is 187 m 2 / g.
[0083] Embodiment 5:
[0084] 1. The vermiculite mineral, goethite and pyrolusite are crushed through a 200-mesh sieve to obtain vermiculite mineral powder, goethite powder and pyrolusite powder with a particle size of ≤0.075 mm.
[0085] 2. The vermiculite mineral powder was calcined at 900°C in an air atmosphere for 4 hours to obtain expanded vermiculite mineral powder.
[0086] 3. Fully mix expanded vermiculite mineral powder, goethite powder and pyrolusite powder in a mass ratio of 5:5:1, evacuate and let stand for 12 hours at a vacuum degree of 9 Pa to accelerate the ion exchange of iron and manganese ions to obtain a mineral mixture.
[0087] 4. The mineral mixture is reduction-calcined at a temperature of 900° C. in a hydrogen atmosphere for 4 hours to obtain a vermiculite-composite nano-zero-valent confined iron-manganese composite material.
[0088] 5. The vermiculite composite nano zero-valent confined iron-manganese composite material and 5-chloro-2-thiophenecarboxylic acid were vacuumed and left to stand for 12 hours at a mass ratio of 5:1. The vacuum range was 9Pa, so that 2,5-thiophene dicarboxylic acid entered the interlayer domain of the vermiculite composite nano zero-valent confined iron-manganese composite material to obtain a low-density vermiculite-based nano zero-valent confined iron-manganese composite complex. The specific surface area of the composite material was 191m 2 / g.
[0089] Embodiment 6:
[0090] 1. The vermiculite mineral, siderite and psilomelane are crushed through a 200-mesh sieve to obtain vermiculite mineral powder, siderite powder and psilomelane powder with a particle size of ≤0.075 mm.
[0091] 2. The vermiculite mineral powder was calcined at 1000° C. in an air atmosphere for 4 hours to obtain expanded vermiculite mineral powder.
[0092] 3. Fully mix expanded vermiculite mineral powder, siderite powder and pyrolusite powder in a mass ratio of 5:2:1, evacuate and let stand for 12 hours at a vacuum degree of 10Pa to accelerate the ion exchange of iron and manganese ions to obtain a mineral mixture.
[0093] 4. The mineral mixture is reduction-calcined at a temperature of 1000° C. in a hydrogen atmosphere for 4 hours to obtain a vermiculite-composite nano-zero-valent confined iron-manganese composite material.
[0094] 5. The vermiculite composite nano zero-valent confined iron-manganese composite material and 5-bromo-2-thiophenecarboxylic acid were placed in a mass ratio of 5:1 and vacuumed for 12 hours with a vacuum degree of 10Pa to allow 2,5-thiophenedicarboxylic acid to enter the interlayer domain of the vermiculite composite nano zero-valent confined iron-manganese composite material to obtain a low-density vermiculite-based nano zero-valent confined iron-manganese composite complex. The specific surface area of the composite material is 277m 2 / g.
[0095] Comparative Example:
[0096] 1. Iron-containing nanominerals
[0097] The limonite was crushed through a 200-mesh sieve to obtain limonite powder with a particle size of 0.075 mm. The specific surface area of the mineral is 11 m 2 / g, spare.
[0098] 2. Manganese-containing nanominerals
[0099] The pyrolusite was crushed through a 200-mesh sieve to obtain pyrolusite powder with a particle size of 0.075 mm. The specific surface area of the mineral is 15 m 2 / g, spare.
[0100] 3. Nano zero-valent iron composite materials
[0101] The limonite was crushed through a 200-mesh sieve to obtain limonite powder with a particle size of 0.075 mm, which was calcined at 800°C in a hydrogen atmosphere for 4 hours to obtain a nano zero-valent iron composite material with a specific surface area of 21 m 2 / g.
[0102] 4. Nano-manganese composite materials
[0103] The pyrolusite was crushed through a 200-mesh sieve to obtain pyrolusite powder with a particle size of 0.075 mm, which was calcined at 800°C in a hydrogen atmosphere for 4 hours to obtain a nano-manganese composite material with a specific surface area of 25 m 2 / g.
[0104] 5. Nano zero-valent iron-manganese composite materials
[0105] The pyrolusite and limonite were crushed through a 200-mesh sieve to obtain a powder with a particle size of 0.075 mm. The above minerals were mixed in a mass ratio of 1:1 and calcined at 800°C in a hydrogen atmosphere for 4 hours to obtain a nano zero-valent iron-manganese composite material with a specific surface area of 26 m 2 / g.
[0106] 6. Expanded Vermiculite Composite Materials
[0107] The vermiculite mineral was crushed through a 200-mesh sieve to obtain vermiculite mineral powder with a particle size of 0.075 mm. The vermiculite mineral powder was calcined in an air atmosphere at a calcination temperature of 800°C for 4 hours to obtain expanded vermiculite mineral with a specific surface area of 32 m 2 / g.
[0108] 7. Vermiculite composite nano zero-valent iron-manganese composite material
[0109] (1) crushing limonite through a 200-mesh sieve to obtain limonite powder with a particle size of 0.075 mm; crushing pyrolusite through a 200-mesh sieve to obtain pyrolusite powder with a particle size of 0.075 mm; crushing vermiculite through a 200-mesh sieve to obtain vermiculite powder with a particle size of 0.075 mm.
[0110] (2) First, the vermiculite mineral powder was calcined at 800°C in air for 4 hours to obtain expanded vermiculite mineral. The expanded vermiculite mineral powder, limonite powder, and pyrolusite powder were mixed in a mass ratio of 1:1:1 to obtain a mixed mineral material. The mixed mineral material was reduction-calcined at 800°C in a hydrogen atmosphere for 4 hours to obtain a vermiculite composite nano-zero-valent iron-manganese composite material having a specific surface area of 37 m 2 / g.
[0111] 8. Nano-zero-valent iron-based complex composite materials
[0112] The limonite was crushed and passed through a 200-mesh sieve, and then reduced and roasted at 800°C in a hydrogen atmosphere for 4 hours to obtain a nano zero-valent iron composite material. The nano zero-valent iron composite material was mixed with 5-bromo-2-thiophenecarboxylic acid at a mass ratio of 2:1 at room temperature for 12 hours to obtain a nano zero-valent iron-based complex composite material with a specific surface area of 28 m 2 / g.
[0113] 9. Nano-Zero-Valent Manganese-Based Complex Composite Materials
[0114] The pyrolusite was crushed and passed through a 200-mesh sieve, and calcined at 800°C in a hydrogen atmosphere for 4 hours to obtain a nano-manganese composite material. The nano-manganese composite material was mixed with 5-bromo-2-thiophenecarboxylic acid at a mass ratio of 2:1 at room temperature for 12 hours to obtain a nano-manganese-based complex composite material with a specific surface area of 33 m 2 / g.
[0115] 10. Preparation of nano zero-valent iron-based complex composite materials based on iron salts
[0116] The iron salt was reduced in sodium borohydride to obtain a nano zero-valent iron composite material. The nano zero-valent iron composite material was mixed with 5-bromo-2-thiophenecarboxylic acid at a mass ratio of 2:1 at room temperature for 12 hours to prepare a nano zero-valent iron-based complex composite material. The specific surface area of the material was 24m 2 / g.
[0117] 11. Preparation of nano zero-valent manganese-based complex composite materials based on manganese salts
[0118] Manganese salt was reduced in sodium borohydride to obtain a nano manganese composite material. The nano manganese composite material was mixed with 5-bromo-2-thiophenecarboxylic acid at a mass ratio of 2:1 at room temperature for 12 hours to prepare a nano zero-valent manganese-based complex composite material. The specific surface area of the material was 17 m 2 / g.
[0119] 12. Iron salt-based complex composite materials
[0120] The iron salt and 5-bromo-2-thiophenecarboxylic acid were stirred and mixed at a mass ratio of 2:1 at room temperature for 12 hours to prepare a trivalent iron-based complex composite material with a specific surface area of 14 m 2 / g.
[0121] 13. Manganese salt-based complex composite materials
[0122] Manganese salt and 5-bromo-2-thiophenecarboxylic acid were stirred and mixed at room temperature for 12 hours in a mass ratio of 2:1 to prepare a manganese-based complex composite material with a specific surface area of 19 m 2 / g.
[0123] 14. Vermiculite composite trivalent iron-based complex composite material
[0124] The vermiculite mineral was calcined at 700°C in air for 4 hours to obtain expanded vermiculite mineral. The expanded vermiculite mineral, iron salt and 5-bromo-2-thiophenecarboxylic acid were stirred and mixed at room temperature for 12 hours in a mass ratio of 5:2:1 to prepare a vermiculite composite trivalent iron-based complex composite material with a specific surface area of 30 m 2 / g.
[0125] 15. Vermiculite composite manganese-based complex composite materials
[0126] The vermiculite mineral was calcined at 700°C in air for 4 hours to obtain expanded vermiculite mineral. The expanded vermiculite mineral, manganese salt and 5-bromo-2-thiophenecarboxylic acid were stirred and mixed at room temperature for 12 hours in a mass ratio of 5:2:1 to prepare a vermiculite mineral-based manganese complex composite material with a specific surface area of 36 m 2 / g.
[0127] 16. Vermiculite mineral composite materials
[0128] (1) Vermiculite, siderite and psilomelane are crushed and passed through a 200-mesh sieve to obtain vermiculite powder, siderite powder and psilomelane powder with a particle size of 0.075 mm.
[0129] (2) Vermiculite powder, siderite powder and psilomelane powder are fully mixed in a mass ratio of 5:2:1 to obtain a mineral mixture.
[0130] (3) The mineral mixture is reduction-calcined at a temperature of 900° C. in a hydrogen atmosphere for 4 hours to obtain a vermiculite-composite nano-zero-valent iron-manganese composite material.
[0131] (4) The vermiculite composite nano-zero-valent iron-manganese composite material and 5-bromo-2-thiophenecarboxylic acid were mixed at a mass ratio of 5:1 at room temperature for 12 hours to prepare a vermiculite mineral composite material having a specific surface area of 89 m 2 / g.
[0132] 17. Biomass carbon-based iron-manganese composite materials
[0133] (1) The straw, hematite, and rhodochrosite were crushed and passed through a 200-mesh sieve to obtain straw powder, hematite powder, and rhodochrosite powder with a particle size of 0.075 mm.
[0134] (2) The straw powder, hematite powder and rhodochrosite powder are fully mixed in a mass ratio of 5:2:1 to obtain a mineral mixture.
[0135] (3) The mineral mixture was pyrolyzed and calcined at 800°C in a nitrogen atmosphere for 4 hours to obtain a biomass carbon-based iron-manganese composite material with a specific surface area of 77 m 2 / g.
[0136] Test example:
[0137] The nano mineral-based catalysts prepared in Examples 1-6 and Comparative Examples 1-17 were added to new pollutants containing oxytetracycline, cyclotriphosphazene and diflorasone, respectively. The amount of the nano mineral-based catalyst added was 0.1 g / L, the concentration of the new pollutant was set to 100 mg / L, the pH value was 7, the concentration of sodium persulfate was 0.5 g / L, and the duration of the catalytic reaction was 5 hours. In each reaction system, water samples were collected regularly to test the concentration change of the new pollutant after the reaction.
[0138] As can be seen from Tables 1 and 2, the degradation rate of oxytetracycline in Example 1-6 reached 100% at 10 minutes of reaction, and within 5 hours of reaction, the mineralization rate ranged from 80% to 93%, showing a high mineralization efficiency. As can be seen from Tables 3 and 4, the degradation rate of cyclotriphosphazene in Example 1-6 also reached 100% at 30 minutes of reaction, and within 5 hours of reaction, the mineralization rate ranged from 79% to 97%, showing a good mineralization effect. As can be seen from Tables 5 and 6, the degradation rate of diflorasone in Example 1-6 reached 100% at 30 minutes of reaction, and within 5 hours of reaction, the mineralization rate ranged from 87% to 97%, also showing a high mineralization efficiency. These results show that the introduction of thiophene carboxylic acid ligands into the low-density vermiculite-based nano zero-valent iron-manganese mineral composite complex and sodium persulfate system helps to improve the degradation rate and reaction rate of sodium sulfate catalytic oxidation of new polluted wastewater under the action of nano-confinement effect.
[0139] Tables 7 and 8 show the degradation rate and mineralization rate of oxytetracycline by comparative examples 1-17. It can be seen from the table that within 5 hours of reaction, the range of catalytic degradation rate is 18%-71%, and the range of mineralization rate is 3%-17%. This shows that the various mineral-based catalysts prepared by comparative examples 1-17 are less efficient in catalytic degradation of oxytetracycline, and the degradation rate is slow. Tables 9 and 10 show the degradation rate and mineralization rate of cyclotriphosphazene by comparative examples 1-17. Within 5 hours of reaction, the range of catalytic degradation rate is 8%-59%, and the range of mineralization rate is 2%-23%. It can also be seen that the degradation effect of the mineral-based catalysts prepared by comparative examples 1-17 on cyclotriphosphazene is poor, and the degradation rate is slow. Tables 11 and 12 show the degradation rate and mineralization rate of diflorasone by comparative examples 1-17. Within 5 hours of reaction, the range of catalytic degradation rate is 5%-37%, and the range of mineralization rate is 2%-21%. This further indicates that the mineral-based catalysts prepared in Comparative Examples 1-17 perform poorly in the catalytic degradation of diflorasone and have a slow reaction rate.
[0140] The specific analysis is as follows: the uncalcined iron-containing nano-minerals and manganese-containing nano-minerals in Comparative Examples 1 and 2 have a small specific surface area and a low surface activity, and therefore exhibit a low degradation rate and mineralization rate, and the catalytic degradation rate and mineralization rate are also slow. The nano-zero-valent iron composite material, nano-manganese composite material, and nano-zero-valent iron-manganese composite material in Comparative Examples 3, 4, and 5 are easy to passivate, resulting in low degradation rates and mineralization rates, and the catalytic degradation rate and mineralization rate are also limited. The calcined vermiculite in Comparative Example 6 also has a low degradation rate and mineralization rate due to the small amount of metal elements it contains, and the catalytic degradation rate and mineralization rate are slow. The vermiculite-composite nano-zero-valent iron-manganese composite material in Comparative Example 7 also exhibits a low degradation rate and mineralization rate, and the catalytic degradation rate and mineralization rate are not high. The reason is that the lack of organic ligands reduces the activity of the composite material. The materials prepared in Comparative Examples 8 to 13 did not add expanded vermiculite as a substrate, which caused the materials to easily agglomerate, thereby affecting the degradation rate and mineralization rate of new pollutant wastewater, and the catalytic degradation rate and mineralization rate also slowed down. In Comparative Examples 14 and 15, the vermiculite composite trivalent iron-based complex and the vermiculite composite manganese-based complex are single metal-based complex materials, which are easily interfered by other ions, and the materials prepared by iron salts and manganese salts are easy to agglomerate, resulting in catalyst deactivation, thus showing a lower degradation rate and mineralization rate, as well as a slower catalytic degradation rate and mineralization rate. The vermiculite mineral composite material of Comparative Example 16 was not vacuum pre-treated, resulting in the composite material failing to form a nano-confinement effect, and therefore showing a lower degradation rate and mineralization rate, and the catalytic degradation rate and mineralization rate are also slower. The biochar-based iron-manganese composite material of Comparative Example 17 lacks interlayer domains in the biochar and no vacuum pretreatment is performed during the preparation process, resulting in the inability to form a nano-confinement effect. As a result, it also shows a lower degradation rate and mineralization rate, as well as a slower catalytic degradation rate and mineralization rate.
[0141] Figure 1 This is the XRD diagram of pyrite. It can be seen from the figure that the diffraction peaks at 2θ = 29.42°, 32.1°, 38.10°, 41.89°, 48.50°, 57.30°, 62.70°, and 65.30° are the characteristic diffraction peaks of pyrite, which belong to the characteristic diffraction peaks of different crystal planes of pyrite.
[0142] Figure 2 This is the XRD diagram of limonite. It can be seen from the figure that the diffraction peaks at 2θ=21.2°, 33.3°, 34.8°, and 36.8° are characteristic diffraction peaks of goethite. The diffraction peaks at 2θ=26°, 42°, and 55° are characteristic diffraction peaks of quartz, indicating that limonite is mainly composed of goethite and quartz.
[0143] Figure 3The XRD diagram of siderite shows that the characteristic peaks of siderite are at 2θ=25°, 33°, 37°, 43°, 45°, 52°, 53.5°, and 62.5°. The characteristic diffraction peaks of quartz are at 2θ=24.5° and 27.8°. The characteristic diffraction peaks of goethite are at 2θ=18°, 22°, 34°, 35°, and 37°. It can be seen that the main components of natural siderite are siderite, quartz, and goethite.
[0144] Figure 4 This is the XRD diagram of manganese ore. It can be seen from the figure that the diffraction peaks at 2θ=30°, 39°, and 58° are characteristic diffraction peaks of pyrolusite, and the diffraction peaks at 2θ=22°, 28°, 38°, 40°, 52°, and 61° are characteristic peaks of quartz. It can be seen that manganese ore is composed of pyrolusite and quartz.
[0145] Figure 5 Figures A and B are SEM images of limonite. It can be seen from the figure that the microstructure of limonite presents a honeycomb and needle-like morphology, indicating that limonite is mainly composed of goethite, hematite and quartz. The microscopic length of limonite crystals is generally between 500nm-2μm.
[0146] Figure 6 Figure 1 is a SEM image of Example 1, where AD is a different magnification. Figure 6 It can be seen that the low-density vermiculite-based nano-zero-valent confined iron-manganese mineral composite complex presents a nanorod-like morphology and is evenly distributed. Its nanorod-like microstructure has a diameter of about 2 nm and a length of about 10 nm, and has high activity.
[0147] Figure 7 The SEM images of Example 2, wherein AC are different magnifications. Figure 7 A shows that a large number of nanoparticles with a diameter of 20 μm appear in the microstructure of the low-density vermiculite-based nano-zero-valent confined iron-manganese mineral complex. Figure 7 (BC), it can be seen that a large number of colloidal particles appear on the surface of the nanoparticles. This is because the organic ligands enter the interlayer domain of the vermiculite mineral-based nano-zero-valent confined iron-manganese mineral through vacuum extraction, forming highly active catalytic sites.
[0148] Figure 8 The SEM images of Example 3, wherein AD are different magnifications. Figure 8In the middle AD figure, it can be seen that the microstructure of the low-density vermiculite-based nano-zero-valent confined iron-manganese mineral complex has a large number of flaky nanoparticles, which come from the expanded vermiculite mineral. Between the flaky nanoparticles (B), some fine nanoparticles can be observed, which is due to the successful anchoring of the nano-zero-valent iron-manganese in the interlayer domain of the expanded vermiculite mineral by vacuuming. In addition, some colloidal nanoparticles (CD) are observed, which come from the composite of the organic ligand after vacuuming.
[0149] Fig. 9 Figure 4 is the SEM image of Example 4, where AC is a different magnification. Fig. 9 (AC) It can be seen that the microstructure of the low-density vermiculite-based nano-zero-valent confined iron-manganese mineral composite complex shows a large number of nano-sheet structures, and a large number of colloidal nanoparticles are anchored on the outer surface of the nano-sheet structure, which mainly come from the nano-zero-valent iron-manganese composite material and organic ligands. This nanostructured morphology makes it have higher activity.
[0150] Fig.10 Figure 5 is the SEM image of Example 5, where AC is a different magnification. Fig.10 (AC) It can be seen that the microstructure of the low-density vermiculite-based nano-zero-valent confined iron-manganese mineral composite complex shows a large number of petal-shaped nanostructures. This nanostructure morphology is due to the porous structure formed by the dehydration of the mixed minerals after reduction roasting at high temperature, which makes it have higher activity.
[0151] Fig.11 Figure 6 is the SEM image of Example 6, where AC is a different magnification. Fig.11 (AC) It can be seen that the microstructure of the low-density vermiculite-based nano-zero-valent confined iron-manganese mineral composite complex shows a large number of flaky nanostructures and colloidal nanoparticles. These nanoparticles are anchored in the interlayer domain of expanded vermiculite, making it highly active and able to efficiently catalyze the degradation of new pollutants.
[0152] Fig.12 (AD) is the SEM image of manganese minerals. It can be seen from the figure that its microstructure presents stalactite, kidney-shaped and grape-shaped aggregates. It is mainly composed of pyrolusite and also contains a small amount of quartz. This is a special morphology formed under natural geological environment conditions.
[0153] Depend on Fig.13 This is a crystal structure model diagram of vermiculite. It can be seen from the figure that vermiculite belongs to the monoclinic system. Vermiculite is a layered magnesium-containing hydroaluminosilicate secondary metamorphic mineral. The original ore looks like mica and is usually mainly formed by hydrothermal alteration or weathering of black (gold) mica.
[0154] Depend on Fig.14This is a crystal structure model diagram of goethite. It can be seen from the figure that the crystal structure of goethite belongs to the triclinic system. Its basic structural unit is a tetrahedron, which is composed of oxygen ions and iron ions. Iron is located at the center of the tetrahedron and is surrounded by oxygen ions on eight sides. The oxygen ions are located at the vertices of the tetrahedron and are connected to the four surrounding iron ions. The crystal structure of goethite can be regarded as a combination of several tetrahedral units, each of which is connected by a common edge or a common face.
[0155] Depend on Fig.15 The crystal structure model diagram of siderite shows that siderite belongs to the trigonal system. Its crystal is rhombohedral. The crystal structure of siderite is composed of iron ions (Fe 2+ ) and carbonate ions (CO3 2- ). In the crystal structure of siderite, the iron ions occupy octahedral space and are bound to six CO3 2- ions are adjacent, and each CO3 2- The ion is adjacent to three iron ions.
[0156] Depend on Fig.16 The crystal structure model diagram of pyrite shows that pyrite belongs to the isometric crystal system. Its structure is a NaCl type crystal structure. The Fe atoms are located at the corners and face centers of the pyrite unit cell, and the S atoms form a sulfur [S2] 2- , distributed in a dumbbell shape, located at the body center and edge center of the pyrite unit cell, [S2] 2- The axial direction is the same as the diagonal direction of a cube with a size of 1 / 8 of the unit cell, but they do not intersect. SS is a covalent bond with a spacing of 0.21nm.
[0157] Depend on Fig.17 This is a crystal structure model diagram of hematite. It can be seen from the figure that the crystal structure of hematite is composed of iron ions and oxygen ions. Hematite belongs to the hexagonal oxide mineral. Its crystal structure is different from corundum in that Al 3+ The positions are alternately 3+ and Ti 4+ The c-slip plane disappears and the symmetry of the ilmenite lattice decreases.
[0158] Depend on Fig.18The crystal structure model diagram of manganese ore shows that manganese ore forms various variants due to different connection modes of cationic octahedrons. Manganese ore can form different chain structures such as single chain, double chain and triple chain through the common corner vertices and edges of [MnO6] octahedrons. At the same time, manganese ore has a pore structure, and its pore shape is approximately square or rectangular. It has catalytic effect, particle size effect, redox property, molecular sieve and other capabilities. Manganese is a variable valence metal element, and its valence state can range from -2 to +7. There may be manganese elements of various valence states in the manganese-containing nano-mineral phase, which makes the manganese-containing nano-mineral have different mineral species. Its variable valence states increase the chemical reaction activity of manganese-containing nano-minerals and promote the wide application of manganese-containing nano-minerals.
[0159] Depend on Fig.19 The AD diagram shows the microstructure of natural vermiculite mineral, which has a dense structure and low porosity, which is formed due to the natural geological environment.
[0160] Depend on Fig. 20 As can be seen from the AD diagram, the vermiculite mineral calcined at 400°C presents a large number of nanoparticles, but the structure is generally dense.
[0161] Depend on Fig.21 As can be seen from the AD diagram, the vermiculite mineral calcined at 500°C exhibits a large number of nanoparticles and flaky nanomorphologies; and compared with the vermiculite calcined at 400°C, the number of nanoparticles increases further, and a large number of flaky nanomorphologies appear.
[0162] Depend on Fig. 22 It can be seen from the AD graph that the vermiculite mineral calcined at 600℃ presents nanoparticles and nanosheet structures. Moreover, compared with the calcination at 500℃, the number of nanoparticles is further increased, and a nanoplate-like structure morphology appears, and a large number of nanoparticles appear on the nanoplate-like structure morphology.
[0163] Depend on Fig.23 As can be seen from the AD graph, nanoparticles appear on the surface of the vermiculite mineral calcined at 700°C. Compared with the calcination at 600°C, the number of nanoparticles increases further, and a nanoplate-like structure appears. Nanoparticles are found on the nanoplate-like structure, and the number of nanoparticles increases further.
[0164] Depend on Fig.24 It can be seen from the AD graph that the surface of the vermiculite mineral calcined at 800℃ presents nano-flakes and nano-particles. Moreover, compared with the vermiculite mineral calcined at 700℃, its nano-particles and nano-plates are further increased, and nano-particles are found in the nano-plate structure morphology. The nano-plates are further superimposed with micron-structured cracks.
[0165] Depend on Fig.25It can be seen from the AD diagram that a nano-flake morphology appeared on the surface of the vermiculite mineral calcined at 900°C, and compared with its nano-plate-like structure morphology calcined at 800°C, nanoparticles were found on the nano-plate-like structure morphology; and the nano-plate-like morphology showed a sandwich structure morphology, which was formed because the vermiculite mineral was further removed from the chemical state of water under high-temperature calcination.
[0166] Depend on Fig.26 It can be seen from the AD diagram that a large number of nanoparticles and nanosheets appeared on the surface of the vermiculite mineral calcined at 1000℃; and compared with the vermiculite mineral calcined at 900℃, its nanoparticles increased further, and a nanoplate-like structural morphology appeared, and nanoparticles were found on the nanoplate-like structural morphology.
[0167] Fig. 27 (A) is a physical picture of natural vermiculite mineral, from which it can be seen that its morphology is sandy; (B) is a physical picture of expanded vermiculite mineral, from which it can be seen that its morphology is flaky; (C) is a physical picture of natural limonite, from which it can be seen that limonite has a brown morphology; (D) is a physical picture of manganese mineral, from which it can be seen that manganese ore has a black morphology; (E) is a physical picture of low-density vermiculite-based nano-zero-valent confined iron-manganese composite complex, from which it can be seen that it has a red morphology.
[0168] Fig.28 (A) shows the sedimentation phenomenon of natural vermiculite mineral when immersed in water, indicating that its density is greater than that of water, which will lead to excessive energy consumption in the water treatment process; (B) shows the phenomenon that expanded vermiculite mineral is immersed in water and floats on the water surface, indicating that its density is less than that of water; (C) shows the low-density vermiculite mineral-based nano zero-valent confined iron-manganese composite complex suspended in water, which can significantly reduce the energy consumption of water treatment, indicating that the composite material is suitable for treating new pollutants.
[0169] Table 1. Degradation rate of oxytetracycline catalyzed by Examples 1-6
[0170] time 1 minute 5 minutes 10 minutes 30 minutes 1 hour 2 hours 3 hours 4 hours 5 hours Example 1 68 73 100 100 100 100 100 100 100 Example 2 64 84 100 100 100 100 100 100 100 Example 3 74 89 100 100 100 100 100 100 100 Example 4 79 90 100 100 100 100 100 100 100 Example 5 84 94 100 100 100 100 100 100 100 Example 6 82 96 100 100 100 100 100 100 100
[0171] Table 2. Mineralization rate of oxytetracycline catalytic degradation in Examples 1-6
[0172] time 1 minute 5 minutes 10 minutes 30 minutes 1 hour 2 hours 3 hours 4 hours 5 hours Example 1 13 25 37 56 76 80 83 86 90 Example 2 7 16 28 42 65 70 76 84 88 Example 3 9 14 19 36 63 73 85 87 93 Example 4 15 27 31 41 54 66 69 74 87 Example 5 4 11 29 32 49 50 64 77 91 Example 6 12 15 27 30 42 56 68 70 80
[0173] Table 3. Degradation rate of cyclotriphosphazene by catalytic degradation of Examples 1-6
[0174] time 1 minute 5 minutes 10 minutes 30 minutes 1 hour 2 hours 3 hours 4 hours 5 hours Example 1 24 62 78 100 100 100 100 100 100 Example 2 11 32 89 100 100 100 100 100 100 Example 3 32 48 59 100 100 100 100 100 100 Example 4 25 32 79 100 100 100 100 100 100 Example 5 36 48 95 100 100 100 100 100 100 Example 6 27 37 98 100 100 100 100 100 100
[0175] Table 4. Mineralization rate of catalytic degradation of cyclotriphosphazene in Examples 1-6
[0176] time 1 minute 5 minutes 10 minutes 30 minutes 1 hour 2 hours 3 hours 4 hours 5 hours Example 1 8 12 31 47 69 72 80 84 97 Example 2 11 22 34 43 53 67 79 80 90 Example 3 14 23 27 30 36 40 50 66 86 Example 4 6 18 24 36 41 53 75 78 89 Example 5 10 17 18 25 34 51 63 72 82 Example 6 3 13 20 24 36 42 53 65 79
[0177] Table 5. Degradation rate of diflorasone catalytically degraded in Examples 1-6
[0178] time 1 minute 5 minutes 10 minutes 30 minutes 1 hour 2 hours 3 hours 4 hours 5 hours Example 1 42 58 66 100 100 100 100 100 100 Example 2 41 53 73 100 100 100 100 100 100 Example 3 51 55 79 100 100 100 100 100 100 Example 4 49 68 86 100 100 100 100 100 100 Example 5 52 63 88 100 100 100 100 100 100 Example 6 49 53 89 100 100 100 100 100 100
[0179] Table 6. Mineralization rate of catalytic degradation of diflorasone in Examples 1-6
[0180] time 1 minute 5 minutes 10 minutes 30 minutes 1 hour 2 hours 3 hours 4 hours 5 hours Example 1 2 9 10 18 35 48 69 76 95 Example 2 11 15 18 19 26 34 39 59 94 Example 3 3 5 16 22 26 36 65 74 89 Example 4 10 16 18 19 31 35 76 88 94 Example 5 17 18 19 21 32 45 57 69 87 Example 6 4 7 10 25 47 51 66 78 97
[0181] Table 7. Degradation rate of oxytetracycline by catalytic degradation of comparative examples 1-17 (%)
[0182]
[0183]
[0184] Table 8. Mineralization rate of oxytetracycline catalytic degradation in comparative examples 1-17 (%)
[0185] time 1 minute 5 minutes 10 minutes 30 minutes 1 hour 2 hours 3 hours 4 hours 5 hours Comparative Example 1 4 4 8 10 15 17 17 17 17 Comparative Example 2 5 6 6 7 7 8 9 11 11 Comparative Example 3 6 6 6 8 8 9 9 10 10 Comparative Example 4 8 9 9 9 10 11 11 11 11 Comparative Example 5 5 7 7 7 7 8 8 8 9 Comparative Example 6 6 8 9 9 10 11 12 12 12 Comparative Example 7 7 7 8 8 9 9 9 9 9 Comparative Example 8 2 3 4 5 7 8 9 9 9 Comparative Example 9 3 4 5 6 7 9 10 10 10 Comparative Example 10 6 9 10 11 12 13 13 13 13 Comparative Example 11 4 4 4 4 4 4 5 6 9 Comparative Example 12 3 6 7 8 9 10 11 13 13 Comparative Example 13 4 4 5 6 7 8 9 10 10 Comparative Example 14 8 8 8 8 8 9 9 9 10 Comparative Example 15 2 5 6 7 8 9 9 9 12 Comparative Example 16 3 6 7 8 9 10 12 12 12 Comparative Example 17 1 1 1 1 2 2 2 3 3
[0186] Table 9. Degradation rate of cyclotriphosphazene by catalytic degradation of comparative examples 1-17 (%)
[0187]
[0188]
[0189] Table 10. Mineralization rate of catalytic degradation of cyclotriphosphazene in comparative examples 1-17 (%)
[0190] time 1 minute 5 minutes 10 minutes 30 minutes 1 hour 2 hours 3 hours 4 hours 5 hours Comparative Example 1 1 2 3 3 3 3 3 3 4 Comparative Example 2 1 1 2 2 2 2 2 2 3 Comparative Example 3 2 2 2 3 3 3 3 3 4 Comparative Example 4 1 2 2 2 2 2 2 2 2 Comparative Example 5 2 2 2 2 3 3 3 3 3 Comparative Example 6 3 3 3 3 3 4 4 4 4 Comparative Example 7 2 2 2 2 2 3 3 3 3 Comparative Example 8 2 4 8 8 8 9 9 9 9 Comparative Example 9 2 2 3 4 5 8 8 8 8 Comparative Example 10 1 1 2 5 7 7 7 7 7 Comparative Example 11 1 9 9 9 9 9 9 9 9 Comparative Example 12 1 1 2 6 7 7 8 8 8 Comparative Example 13 2 7 9 9 10 10 10 10 10 Comparative Example 14 1 2 2 5 6 7 8 8 8 Comparative Example 15 2 2 7 7 7 8 8 8 8 Comparative Example 16 10 14 17 21 22 23 23 23 23 Comparative Example 17 1 1 1 1 1 1 1 1 2
[0191] Table 11. Degradation rate of diflorasone by catalytic degradation of comparative examples 1-17 (%)
[0192]
[0193]
[0194] Table 12. Mineralization rate of diflorasone catalytic degradation in comparative examples 1-17 (%)
[0195] time 1 minute 5 minutes 10 minutes 30 minutes 1 hour 2 hours 3 hours 4 hours 5 hours Comparative Example 1 1 1 3 5 8 9 10 11 13 Comparative Example 2 6 9 10 15 17 18 19 20 21 Comparative Example 3 1 2 7 8 9 10 11 12 13 Comparative Example 4 1 3 4 5 7 8 9 10 11 Comparative Example 5 2 7 8 9 10 11 12 13 14 Comparative Example 6 3 8 8 8 8 9 9 9 9 Comparative Example 7 1 3 3 6 9 9 9 9 9 Comparative Example 8 2 4 8 7 8 8 8 8 8 Comparative Example 9 2 9 10 10 10 11 12 13 14 Comparative Example 10 6 9 10 11 12 13 13 13 14 Comparative Example 11 1 6 8 9 9 10 11 12 13 Comparative Example 12 1 5 5 6 7 8 8 8 8 Comparative Example 13 2 7 9 9 10 10 10 10 10 Comparative Example 14 1 2 3 5 6 7 8 9 10 Comparative Example 15 2 3 4 7 8 9 9 9 9 Comparative Example 16 1 2 3 3 3 3 3 5 8 Comparative Example 17 1 1 1 1 1 1 1 2 2
Claims
1. A method for preparing a low-density vermiculite-based nanometer zero-valent confined iron-manganese composite complex, characterized in that The steps include: Step 1: respectively crushing the vermiculite mineral, the manganese-containing nano-mineral and the iron-containing nano-mineral through a 200-mesh sieve to obtain vermiculite mineral powder, manganese-containing nano-mineral powder and iron-containing nano-mineral powder; Step 2: calcining the vermiculite mineral powder at 500-1000° C. in an air atmosphere for 2-5 hours to obtain expanded vermiculite mineral powder; Step 3: Mix the expanded vermiculite mineral powder, the manganese-containing nano-mineral powder and the iron-containing nano-mineral powder, evacuate and let stand for 12-24 hours, which can accelerate the ion exchange of iron and manganese ions and enter the interlayer domain of the expanded vermiculite mineral; then reduce and roast the composite material in a hydrogen atmosphere to obtain a vermiculite-based nano zero-valent confined iron-manganese composite material; Step 4: Mix the vermiculite-based nano zero-valent confined iron-manganese composite material with the thiophene carboxylic acid ligand, evacuate and let stand for 12-24 hours, the vacuum degree range is 0.1Pa-10Pa, this process allows the thiophene carboxylic acid ligand to enter the interlayer domain of the vermiculite-based nano zero-valent confined iron-manganese composite material to obtain a low-density vermiculite-based nano zero-valent confined iron-manganese composite complex.
2. The preparation method according to claim 1, characterized in that: In step 3, the mass ratio of expanded vermiculite mineral powder, manganese-containing nano-mineral powder and iron-containing nano-mineral powder is 1-5:1-5:
1.
3. The preparation method according to claim 1, characterized in that: In step 3, when the vacuum is evacuated and left to stand, the vacuum degree ranges from 0.1Pa to 10Pa.
4. The preparation method according to claim 1, characterized in that: In step 3, the calcination temperature is 500-1000° C. and the calcination time is 2-5 hours.
5. The preparation method according to claim 1, characterized in that: In step 4, the thiophene carboxylic acid ligand is selected from any one of 2,5-thiophenedicarboxylic acid, 5-methyl-2-thiophenecarboxylic acid, 4-bromo-2-thiophenecarboxylic acid, 5-chloro-2-thiophenecarboxylic acid, and 5-bromo-2-thiophenecarboxylic acid.
6. The preparation method according to claim 5, characterized in that: The mass ratio of the vermiculite-based nanometer zero-valent confined iron-manganese composite material to the thiophene carboxylic acid ligand is 1-5:
1.
7. Use of the low-density vermiculite-based nano zero-valent confined iron-manganese composite complex prepared according to any one of the preparation methods of claims 1 to 6 in the deep treatment of new pollutants.
8. The use according to claim 7, characterized in that: The low-density vermiculite-based nanometer zero-valent confined iron-manganese composite complex is mixed with persulfate for deep treatment of new pollutants; the persulfate is peroxymonosulfate or peroxydisulfate.
9. The use according to claim 8, characterized in that: In the treatment system, the concentration of the low-density vermiculite-based nano zero-valent confined iron-manganese complex is 0.1-10 g / L, the concentration of persulfate is 1-10 g / L, and the concentration of the new pollutant is 0.1-1000 mg / L.
10. The use according to claim 7 or 9, characterized in that: The new pollutants include at least one of antibiotics, flame retardants and fluorides.